Sp1 binding sites inserted into the rous sarcoma virus long terminal repeat enhance LTR-driven gene expression - Machon, O; Strmen, V; Hejnar, J; Geryk, J; Svoboda, J (Gene, 1998)
Although the Rous sarcoma virus (RSV) long terminal repeat (LTR) is an efficient promoter of transcription, most RSV proviruses are down-regulated upon retroviral integration in non-permissive mammalian cells. Among other mechanisms, DNA methylation has been shown to be involved in proviral silencing. The presence of Sp1 binding sites has been demonstrated to be essential for protection of a CpG island and also non-island DNA regions from de novo methylation. Also, the presence of these sites in the LTRs correlates with the transcriptional activity of certain proviral structures. Using transient and stable transfection assays, we demonstrate that insertion of Sp1 binding sites into the RSV LTR remarkably increases expression of the LTR-driven genes in permissive and non-permissive cells, despite the reported negative effect of insertion of the non-specific DNA into the LTR promoter/enhancer sequences. Particular arrangement of inserted Sp1 sites was effective even in stably transfected reporter gene constructs into non-permissive mammalian cells, where additional factors exert negative effects on expression.
Keywords: transfekce; DNA Methylation; Sp1 Transcription Factor; Cell Line; Plasmids; vazebná místa; metylace DNA; Transfection; Gene Expression Regulation, Viral; reportérové geny; Repetitive Sequences, Nucleic Acid; viry ptačího sarkomu; transkripční faktor Sp1; Avian Sarcoma Viruses; Binding Sites; Animals; zvířata; plazmidy; nádorové buňky kultivované; buněčné linie; repetitivní sekvence nukleových kyselin; Tumor Cells, Cultured; Genes, Reporter; regulace exprese virových genů